Phân tích phổ khối lượng của một số phức chất Ni(II) với thiosemicacbazon - Kính và cộng sự, Chu Đình (Vietnam Journal of Chemistry, 2014)
Three new Ni(II) complexes of thiosemicarbazone were synthesized and characterized by their MS/ MS2/MS3 spectra. Typical characteristics and fragmentation schemes of these complexes were observed. Base on detailed analysis of fragment picks the mechanisms of unimolecular ion decompositions of Ni(II) complexes were proposed.